2016
DOI: 10.1016/j.msea.2016.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, texture and mechanical properties in a low carbon steel after ultrafast heating

Abstract: Microstructure, texture and mechanical properties in a low carbon steel after ultrafast heating. AbstractHeating experiments in a wide range of heating rates from 10 to 1200 °C/s and subsequent quenching without isothermal soaking have been carried out on a low carbon steel. The thermal cycles were run on two different cold rolled microstructures, namely ferrite + pearlite and ferrite + martensite. It is shown that the average ferritic grain size, the ferrite grain size distribution, the phase volume fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…Liu and Argen et al [6,7] observed the precipitation of austenite as Widmanstätten plates in Fe-Cr-C steels due to Cr enrichment of the cementite outer layer. More recently, austenite growth was studied by Cerda et al [18][19][20] under ultrafast heating rates, indicating that local C concentration is responsible for changes in the mechanism of austenite formation. In addition, De Knijf et al [21], and Cerda et al, [22] studied the effect of ultrafast heating on recrystallization, showing that nucleation of recrystallized ferrite grains is enhanced by increasing the heating rate and results in refined microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Argen et al [6,7] observed the precipitation of austenite as Widmanstätten plates in Fe-Cr-C steels due to Cr enrichment of the cementite outer layer. More recently, austenite growth was studied by Cerda et al [18][19][20] under ultrafast heating rates, indicating that local C concentration is responsible for changes in the mechanism of austenite formation. In addition, De Knijf et al [21], and Cerda et al, [22] studied the effect of ultrafast heating on recrystallization, showing that nucleation of recrystallized ferrite grains is enhanced by increasing the heating rate and results in refined microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Although very fast heating rates have been applied in the case hardening of the structural steels, ultrafast heating (UFH) of flat steel products is now considered to be among the new processing routes [1][2][3][4][5]. A recent study on cold-rolled low carbon steel [5] shows that both strength and ductility can be enhanced at the same time after the application of ultrafast heating rates.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on cold-rolled low carbon steel [5] shows that both strength and ductility can be enhanced at the same time after the application of ultrafast heating rates. The improvement in mechanical properties stems from the variety of microstructures resulting from the application of UFH.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of austenite formation, the analogy holds as very fast heating rates shift the onset of austenite formation to high temperatures. The martensitic structure‐refining effect observed in samples heated at UFH rates reported elsewhere is a consequence of the enhanced nucleation of austenite on heating. In Figure d–f, different nucleation sites are shown for austenite (martensite).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were cut from each heat‐treated specimen. As in previous studies, the zone of homogeneous microstructure in each specimen was determined by plotting the Vickers hardness (HV3) measured in the TD plane (i.e., the plane perpendicular to TD of the cold rolled sheet) as a function of the distance along the RD direction. Subsequent characterization and data collection were performed within the limits of the homogeneous zone.…”
Section: Methodsmentioning
confidence: 99%